A Lamp to Light the Way: Public Health Nurses’ Perceptions and Experiences of Professional/Clinical Supervision - Farrell, Elizabeth (Auckland University of Technology, 2003)
Clinical supervision is a relatively new concept in nursing with no New Zealand research on the topic to date. However taking a lead from our colleagues in Britain and elsewhere, clinical supervision is gaining momentum in nursing in this country because of the perceived benefits it can have for both nurses and clients. This study sought answers to the question ‘What are Public Health Nurses’ perceptions and experiences of clinical supervision?’ It consisted of a comprehensive literature review and a small qualitative descriptive research project. As part of the study, two focus group interviews involving seven PHNs were conducted. The data analysis uncovered a developmental process that the participant PHNs went through as they began to understand the principles of clinical supervision and began to relate their practice to the peer reciprocal model of supervision, which had recently been introduced to their organisation. Four key themes were identified - ‘needing’, ‘knowing’, ‘learning’, and ‘doing’ clinical supervision. The study also demonstrated how public health nursing practice was inextricably woven throughout. I have called this process a ‘journey of discovery’. From the participants’ perspective, the rationale for clinical supervision revolved around the perceived need to understand the complexity of this nursing speciality, and in the recognition of the impact this practice had on the PHNs’ personal well-being and subsequent ability to provide competent nursing care. Thus, practice became the ‘essence’ of the peer reciprocal clinical supervision sessions that developed after the introduction of this model. As this is a small qualitative descriptive study, limitations are acknowledged. However, it is hoped that the outcome of this research will improve the understanding of clinical supervision from a public health nursing perspective, facilitate more debate, guide others attempts to introduce clinical supervision and influence future research direction.
Keywords: Public health nurses; Supervision of public health nurses